Isolation and sequencing of doublesex/male abnormal 3 (DM) related transcription factor (Dmrt) genes from the Asian toad Bufo gargarizans (Cantor, 1842) - Wen Chen; Liu-wang Nie; Ping-ping Zheng (Genetics and Molecular Biology, 2007)
The doublesex/male abnormal 3 (dsx/mab-3 or DM) domain gene family involved in sexual development encodes putative transcription factors including a DNA-binding homology motif, the DM domain. We used highly degenerate primers to clone and sequence seven distinct DM related transcription factor (Dmrt) genes from the Asian toad (Bufo gargarizans Cantor, 1842). A database search for the cloned sequences revealed the following percentage identity with the homologous Dmrt genes of the human: BgDmrt1 = 97%, BgDmrt2 = 97%, three isoforms of BgDmrt3 (BgDmrt3a = 93%, BgDmrt3b = 95%, BgDmrt3c = 100%) and two isoforms of BgDmrt5 (BgDmrt5 = 97%, BgDmrt5 = 91%). Based on DM domain amino acid sequence similarities we constructed a phylogenetic tree which grouped vertebrate and invertebrate Dmrt genes into seven distinct subfamilies. The DM domains of both human and the newly-discovered Bufo gargarizans genes contained two conserved zinc-chelating sites (CCHC and HCCC), except BgDmrt3b, which contained the CCRC and HCCC sites.